Diagnostic application of a capture based NGS test for the concurrent detection of variants in sequence and copy number as well as LOH. Issue 3 (15th September 2017) - Vetro, A.; Goidin, D.; Lesende, I.; Limongelli, I.; Ranzani, G.N.; Novara, F.; Bonaglia, M.C.; Rinaldi, B.; Franchi, F.; Manolakos, E.; Lonardo, F.; Scarano, F.; et al.
Abstract : Whole exome sequencing (WES) has made the identification of causative SNVs/InDels associated with rare Mendelian conditions increasingly accessible. Incorporation of softwares allowing CNVs detection into the WES bioinformatics pipelines may increase the diagnostic yield. However, no standard protocols for this analysis are so far available and CNVs in non‐coding regions are totally missed by WES, in spite of their possible role in the regulation of the flanking genes expression. So, in a number of cases the diagnostic workflow contemplates an initial investigation by genomic arrays followed, in the negative cases, by WES. The opposite workflow may also be applied, according to the familial segregation of the disease. We show preliminary results for a diagnostic application of a single next generation sequencing panel permitting the concurrent detection of LOH and variations in sequences and copy number. This approach allowed us to highlight compound heterozygosity for a CNV and a sequence variant in a number of cases, the duplication of a non‐coding region responsible for sex reversal, and a whole‐chromosome isodisomy causing reduction to homozygosity for a WFS1 variant. Moreover, the panel enabled us to detect deletions, duplications, and amplifications with sensitivity comparable to that of the most widely used array‐CGH platforms. Abstract :